Postural Control Disturbances Induced by Virtual Reality in Stroke Patients - Charles Morizio; Maxime Billot; Jean-Christophe Daviet; Stéphane Baudry; Christophe Barbanchon; Maxence Compagnat; Anaick Perrochon (Applied Sciences, 2021)
People who survive a stroke are often left with long-term neurologic deficits that induce, among other impairments, balance disorders. While virtual reality (VR) is growing in popularity for postural control rehabilitation in post-stroke patients, studies on the effect of challenging virtual environments, simulating common daily situations on postural control in post-stroke patients, are scarce. This study is a first step to document the postural response of stroke patients to different challenging virtual environments. Five subacute stroke patients and fifteen age-matched healthy adults were included. All participants underwent posturographic tests in control conditions (open and closed eyes) and virtual environment without (one static condition) and with avatars (four dynamic conditions) using a head-mounted device for VR. In dynamic environments, we modulated the density of the virtual crowd (dense and light crowd) and the avoidance space with the avatars (near or far). Center of pressure velocity was collected by trial throughout randomized 30-s periods. Results showed that more challenging conditions (dynamic condition) induced greater postural disturbances in stroke patients than in healthy counterparts. Our study suggests that virtual reality environments should be adjusted in light of obtaining more or less challenging conditions.